Bibliometric analysis of most cited Peyronie's disease and its management publications - Şahin, Mehmet Fatih; Doğan, Çağrı; Akgül, Murat; Yazıcı, Cenk Murat; Şeramet, Serkan; Dayısoylu, Hulusi Sıtkı (Frontiers in Surgery, 2024)
Peyronie's disease (PD) is a common urologic illness, motivating numerous scientific investigations and publications. Scientific publications have more authors each year. A bibliometric review of the PD literature might help urologists and sexual medicine professionals comprehend publication tendencies in this subject. The current study was aimed at presenting a bibliometric analysis of PD, which is one of the important and trending subjects of andrology. On January 5, 2023, Web of Science scanned documents with the terms Peyronie’s disease” “Peyronie’s disease treatment”, “Peyronie’s disease management”, “Peyronie’s disease surgery” and “Peyronie’s disease injection” from 1975 through 2023. Titles, years, authors, citations, citation indices, journal names, authors' countries of origin, article categories, and funding sources were recorded. “Clinical Efficacy, Safety and Tolerability of Collagenase Clostridium Histolyticum for the Treatment of Peyronie Disease in 2 Large Double-Blind, Randomized, Placebo Controlled Phase 3 Studies” has the most citations and citation index. Most of the T100 articles were published in 2020, primarily in the Journal of Urology. These articles mainly focused on treatment, especially surgeries. All of these articles were in English, and the vast majority of them were by authors from the US who were most frequently collaborated with by other authors. This research analyzed the top 100 PD studies. This research focused on pathophysiology, innovative surgical procedures, and new approaches of PD. It also recommended bigger databases and more financing for research.